Enhancing mathematical problem solving ability through model eliciting activities - Diyastanti, Arum; Dewi, Nuriana Rachmani; Sunarmi, Sunarmi (Unnes Journal of Mathematics Education, 2018)
The main purpose of this research was to comprehensively examine the achievement and improvement of mathematical problem solving ability through the use of Model Eliciting Activities and Problem Based Learning. The research method used was explanatory sequential mixed methods. The research design used was Pretest-Posttest Control Group Design. The research population was grade VII students one of Junior High School in Kudus except students in the favourite class. The sample was taken by simple random sampling technique, so that grade VII F was obtained as experiment class and grade VII E as control class. Qualitative research subject were taken 6 subjects based on the mathematical early ability category. The result of the research showed that (1) the achievement of mathematical problem solving ability of the students who got Model Eliciting Activities had not reach the completeness classically; (2) the achievement and improvement of mathematical problem solving ability of the students who got Model Eliciting Activities were better than the students who got Problem Based Learning; (3) the students who got Model Eliciting Activities tend to be active and brave rather than the students who got Problem Based Learning; and (4) some of the students’ difficulties, students with the high early mathematical ability in the experiment class did not face any difficulties, only the students were not careful in calculating, while in the control class faced the difficulty in making plans at number 4, thus influencing the next indicator. For students with the medium early mathematical ability in the experiment class faced the difficulty in determining the correctness of the answer and were not careful in calculating, while in the control class faced the difficulty in determining the correctness of the answer and making the plan at number 4 thus influencing the next indicator. Lastly, for students with low early mathematical ability in both experiment class and control class, they faced the difficulty in determining the truth of the answer and had not finished working on the four questions because the time provided has been exhausted.